OPERASI PENINDAKAN OBAT TRADISIONAL TANPA IZIN EDAR OLEH BADAN PENGAWAS OBAT DAN MAKANAN DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN - Taufiqurrahman Taufiqurrahman; Busyra Azheri; Rembrandt Rembrandt (UNES Law Review, 2023)
Rapid economic development has created various goods and/or services that can be used and consumed. With the increasing variety of goods and/or services in circulation, and supported by advances in information technology, the distribution is increasingly expanding across national boundaries. So this is also a new demand for the government to oversee the distribution of products that are widely circulated in the market, especially in the health sector. One of the important human needs and cannot be left behind in daily activities is medicine. People's fear of the negative stigma of using modern medicine increases people's desire to seek alternatives to traditional medicine. However, there are many distributions of traditional medicines without a Distribution Permit (TIE) from the Center for Drug and Food Control (BBPOM) in Pekanbaru. Based on this, the researcher examines 1) What is BPOM's responsibility for the circulation of medicinal products without distribution permits in the community. 2) What is the legal protection for consumers who use medicinal products without a Distribution Permit from BPOM. Writing this thesis using the approach empirical juridical. From the results of the study, it was found that the most cases were found at Licensed Drug Stores (TOB) facilities. There are 2 (two) responsibilities of BPOM in conducting supervision, namely: pre-market andpost-market, both are supported by the Drug and Food Control System (SisPOM). The form of legal protection by BPOM is preventive and repressive efforts. Establishing a distribution permit is a preventive action taken by BPOM in carrying out aspects of security, comfort and safety for consumers. Repressive protection, namely by carrying out enforcement operations or spot checks on various drug distribution facilities. Furthermore, if a dispute occurs, it will be resolved through the courts and out of court.